Comparison of Soil Physical Properties in Rice Fields under Conventional and Mulch-No-Tillage Systems - Dika Kesumawati; Abdul Haris (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Comparing different land management systems is crucial for understanding their impact on soil physical properties and rice productivity. This research was conducted in Bangkal Village, Banjarbaru City, as part of the Udara Bersih Indonesia program, which promotes the Mulch No-Tillage system. The study aimed to compare the effects of no-tillage with organic mulch (MNT) and conventional tillage (CT) on soil physical properties and rice yield within a 0.5 ha area under similar environmental conditions. Twelve samples were collected from each land type and analyzed using a quantitative comparative approach with an independent t-test. Parameters observed included water-stable aggregates, bulk density, field water content, COLE index, and rice yield. The results showed that MNT had significantly higher water-stable aggregates (53.05%) than CT (42.85%), as well as a higher field water content (94.94%) compared to CT (68.71%). The COLE index under MNT was lower (0.06; medium category) compared to CT (0.20; very high category), indicating lower shrink–swell potential and better soil stability. Bulk density showed no significant difference between MNT (0.81 g cm-³) and CT (0.88 g cm-³), possibly due to the short implementation period of MNT. Rice yields under MNT reached 4.5 ton/ha and 6.5 ton/ha, while CT produced 3.0 ton ha-1 and 3.6 ton ha-1 during the two planting periods. This study strengthens the empirical evidence that the no-tillage system with organic mulch can improve soil physical quality and enhance agricultural productivity, providing a more sustainable and resilient approach to managing tropical paddy soils.